Chapter Предисловие - Farafonova, Dar'ja (Biblioteca di Studi Slavistici, 2023)
Foreword. Dostoevsky: Paradox, Humor, Deconstruction. A foreword to the present book and to each of the 15 articles that are part of it. While the analysis of humor, paradox, and deliberate deconstruction has generally occupied a marginal position in the study of Dostoevsky's universe, it seems impossible to understand his poetics without pointed attention to these categories. The present book aims to fill the existing gap by focusing on the nature of ambivalent humor, paradoxicality, and methods of "de-automatizing" consciousness through deconstruction. It is precisely the dialogical and paradoxical nature of Dostoevsky's artistic method that enables such different and sometimes contradictory readings.